Pengaruh Dosis dan Lama Pengeringan dengan Karbit (Kalsium Karbida) dalam Proses Degreening Jeruk Bangkinang - Raswen Efendi (Jurnal Sagu, 2007)
The objective of the research was to determine the influence of dosage and storage ripening of Calcium Carbide in degreening process of Bangkinang citrus. The research was set up in Complete Randomized Design with four calcium carbide dosage (20, 25, 50, 75 g/kg) on three duration of storage ripening (3, 4, and 5 days). The result of this research concluded that the best treatment was the degreening process with 50 and 70 g/kg calcium carbide dosage and 4 to 5 days storage ripening. Physical and chemical analysis af citrus from this treatment resulted in 5,083-6,2500 Brik total soluble solid and 0,043-0,77% total acid, while organoleptic test showed average hedonic score of 5 and 4,8-5 (both were extremely like), for colour and flavor, respectively. Key words : Calcium carbide, degreening, citrus.